Pathfinder Associative Networks for the Validation of Improvement in Information Security Teaching - Juan, Arias Masa; Malena, Melo Andrade; Rafael, Martin Espada; Juan Angel, Contreras Vas (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2017)
This article presents the experience of Digital Storytelling realized in the ECTS tutorials of the Information Security subject in order to evaluate the development and evolution of students' knowledge through similarity analysis with Pathfinder networks, questionnaires of satisfaction, and qualitative analysis of the open question evaluations, object of this work, with the final purpose of being able to triangulate the obtained results and to verify the validity of the same ones. Consequently, in this experiment, it is determined that the use of Digital Storytelling in the classroom improves the relationship of very complex concepts that students establish.